PENGARUH ISLAMIC LIFESTYLE, BRAND AWARENESS DAN SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK HIJAB RABBANI DI KOTA PALEMBANG - Ameliah; Muhammad Rusdi; Safira Elfadillah (Lentera Jurnal Manajemen, 2026)
The growth of the Muslim fashion industry in Indonesia, particularly hijab products, has steadily increased annually, driving competition between brands. This situation requires companies to understand the factors influencing consumer decisions, particularly those related to Islamic lifestyle, brand awareness, and social media marketing, which influence purchasing decisions for Rabbani hijab products in Palembang. This study employed a quantitative approach with a purposive sampling technique. The population consisted of consumers residing in Palembang who had purchased and used Rabbani hijab products. A sample of 102 respondents was selected using the hair et al. formula. Data collection was conducted through a questionnaire with a Likert scale. Data analysis techniques used included classical assumption testing, multiple linear regression, and hypothesis testing using SPSS version 25 software. The results showed that Islamic lifestyle had a positive and significant effect on purchasing decisions, as evidenced by a t-value of 2.298 and a significance level of 0.000 < 0.05. Brand awareness also had a positive and significant effect on purchasing decisions, with a t-value of 5.722 and a significance level of 0.000 < 0.05. Furthermore, social media marketing had a positive and significant effect on purchasing decisions, with a t-value of 9.940 and a significance level of 0.000 < 0.05, and was the most dominant variable influencing purchasing decisions. Simultaneously, all three independent variables significantly influenced purchasing decisions, with a coefficient of determination (R²) of 0.914, indicating that 91.4% of the variation in purchasing decisions can be explained by Islamic lifestyle, brand awareness, and social media marketing, while the remaining 8.6% was influenced by factors outside the study. Keywords: Islamic Lifestyle, Brand Awareness, Social Media Marketing, Purchasing Decisions.